Service Quality and Its Impact towards Purchasing Decision - Juwita, Juwita; Elserra Siemin Ciamas (Husnayain Business Review, 2024)
This study aims to determine whether service quality can influence purchasing decisions at CV Surya Mas. Methodology/approach - This research uses quantitative research. The sampling method is Non probability with insidential sampling technique with a sampling of 35 customers who made purchases at CV Surya Mas. Findings - The effect of service quality on customer purchasing decisions can be seen from the basis of decision making in this research using the T test. Where the hypothesis results in the T test there is tcount value on the service quality variable 4.257 > ttable 1.696, so it can be concluded that there is an influence of the service quality variable on the purchasing decision variable.